PERHATIAN DALAM FILM RIDINGTHE LIGHT - Sari, Annisa Rachmatika; Ali, Matius (Capture : Jurnal Seni Media Rekam, 2016)
This paper examines forms of the audience attention in RidingThe Light movies which is produced by the impressions of the object adjustment to structure basic of audience thinking. Here, objects are introducing their self to the audience so that they can be accepted and been awared by them because of their condition.Then, object makes adjustments on twelve categories in the audience brain. For finding the audience attention, theory of photoplay Münsterberg serves as the basis of research assuming that audience processes mentality because there are self adaptation of movies in the human intellection of being in the form of space, time, and causality. Therefore, attention is a one of the audience mentality process when film objects, RidingThe Light, was introducing itself.Keywords : Attention, adjustment, RidingThe Light, and film